Palliative resection of the primary tumour in patients with Stage IV colorectal cancer: systematic review and meta‐analysis of the early outcome after laparoscopic and open colectomy. (29th August 2013) - Yang, T. X.; Billah, B.; Morris, D. L.; Chua, T. C.
Abstract: Aim: Resection of the primary tumour in patients with Stage IV colorectal cancer may be performed to avoid future tumour‐related complications whilst on systemic treatment. We compared the safety and efficacy of laparoscopic and open colectomy in this patient group. Method: PubMed, MEDLINE and the Cochrane Library were searched in the English literature for studies between January 2000 and October 2012 dealing with laparoscopic resection of the primary tumour in Stage IV disease. Single‐arm laparoscopic studies were systematically reviewed. Prospective and retrospective studies were included for meta‐analysis. End‐points include safety, complications, mortality and cancer specific outcome including 5‐year and median survival. Results: Eleven studies comprising 1165 patients undergoing palliative laparoscopic colectomy for Stage IV colorectal cancer were included. Five studies were comparative studies of laparoscopic and open colectomy. The former took longer (pooled mean difference (MD) = 41.52, 95% CI = 11.47–71.56, Z = 2.71, P = 0.007), but resulted in a shorter length of stay (pooled MD = −2.41, 95% CI = −3.84 to −0.99, Z = 3.32, P = 0.0009), with fewer postoperative complications (pooled odds ratio = 0.53, 95% CI = 0.32–0.87, Z = 2.51, P = 0.01) and lower estimated blood loss (pooled MD = −47.71, 95% CI = −80.00 to −15.42, Z = 2.90, P = 0.004). Median survival ranged between 11.4 and 30.1 months. Conclusion: Palliative colectomy performed laparoscopically is associated with a better perioperative outcome than open colectomy. Survival is dependent on the response to systemic chemotherapy.